Correlação entre peroxidação lipídica e níveis de creatina quinase plasmática em jogadores de tênis de campo juvenis durante um período competitivo - Ferreira Antunes Neto, J. M.; Donadon, C. C.; Battibugli Rivera, R. J.; Calvi, R. G. (Brazilian Journal of Biomotricity, 2012)
Exercise induces an increase in oxygen consumption and energy demand. The increase in oxygen consumption leads to increased production of reactive oxygen species (ROS). Depending on your concentration, ROS react with cellular structures such as membranes, components and elements of the mitochondrial DNA, which can lead to death of DNA (apoptosis). The increased athletic performance in recent years is directly related to research that modulate the antioxidant capacity of athletes, reducing the potential oxidative cell. The objective of this study was to investigate the behavior of the levels of lipid peroxidation (TBARS) and liberation of CK plasma enzyme in tennis players in competitive period in order to collaborate in modulating their training loads. Three tests for CK and TBARS were made during this period and all showed the same pattern of variation with significant increases in analysis 2 and 4 in relationship with analysis 1 and a high correlatioship between them (c=0.952). The CK values obtained were: analysis 1 = 235±37 U/L; analysis 2 = 476±34 U/L; analysis 3 = 340±17 U/L; TBARS values were: analysis 1 = 3,27±0,91 nmol/mL; analysis 2 = 5,3±1.15 nmol/mL, analysis 3 = 4,6±0,54 nmol/mL. In conclusion, we suggest that the use of more simplified dosing, such as plasma CK, can indicate the extent of oxidative stress levels installed in the muscle cell, as well as defining index of security required to produce a modulation of training loads.